Stability and Free Radical Production for CO2 and H2 in Air Nanobubbles in Ethanol Aqueous Solution - Zhenyao Han; Hiromi Kurokawa; Hirofumi Matsui; Chunlin He; Kaituo Wang; Yuezou Wei; Gjergj Dodbiba; Akira Otsuki; Toyohisa Fujita (Nanomaterials, 2022)
In this study, 8% hydrogen (H2) in argon (Ar) and carbon dioxide (CO2) gas nanobubbles was produced at 10, 30, and 50 vol.% of ethanol aqueous solution by the high-speed agitation method with gas. They became stable for a long period (for instance, 20 days), having a high negative zeta potential (−40 to −50 mV) at alkaline near pH 9, especially for 10 vol.% of ethanol aqueous solution. The extended Derjaguin, Landau, Verwey, and Overbeek (DLVO) theory was used to evaluate the nanobubble stability. When the nanobubble in ethanol alkaline aqueous solution changed to an acidic pH of around 5, the zeta potential of nanobubbles was almost zero and the decrease in the number of nanobubbles was identified by the particle trajectory method (Nano site). The collapsed nanobubbles at zero charge were detected thanks to the presence of few free radicals using G-CYPMPO spin trap reagent in electron spin resonance (ESR) spectroscopy. The free radicals produced were superoxide anions at collapsed 8%H2 in Ar nanobubbles and hydroxyl radicals at collapsed CO2 nanobubbles. On the other hand, the collapse of mixed CO2 and H2 in Ar nanobubble showed no free radicals. The possible presence of long-term stable nanobubbles and the absence of free radicals for mixed H2 and CO2 nanobubble would be useful to understand the beverage quality.